Berbagai Macam Ilmu dan Cara Memperolehnya - Kokom Komariah; Muhbib Abdul Wahab (VISA: Journal of Vision and Ideas, 2024)
Humans are considered to be the most perfect creatures created by God because they are given the gift of knowledge and reason. This view is reflected in Qur'anic verses, such as Surah Al-Alaq (1-5), Surah Taha (20:114), and Surah Al-Mujadalah (58:11), which emphasize the importance of reading, studying, and social cooperation. Knowledge is considered a gift from God that distinguishes humans from the rest of His creation. The Qur'an encourages people to read and pursue knowledge, conveys social ethics, and promises rewards for believers and the knowledgeable.Philosophy of science views science from various perspectives, including empiricism, rationalism, skepticism, positivism, constructivism, pragmatism, realism, idealism, naturalism, and hermeneutics. Each of these views provides a unique perspective on the sources, means and nature of knowledge. Science is categorized into natural sciences, social sciences, humanities, applied sciences, formal sciences, empirical sciences, normative sciences, and fundamental vs. applied sciences. In its historical development, science developed through the Ancient Greeks, the Middle Ages, the Modern Ages, and the Contemporary Ages. Science is colored by approaches such as empiricism, rationalism, and pragmatism. Knowledge and science are considered philosophically, with the difference between knowledge and science. Knowledge is identified with facts or information, while science demands systematization and methodology. In everyday language, the two are often equated. Understanding science plays an important role in dealing with technological advances and the challenges of the times. Philosophy of science provides a conceptual framework for understanding various approaches to acquiring knowledge, from empirical experience to normative considerations. Awareness of the importance of science and knowledge is understood as an effort to get closer to God's wisdom and enrich human life experience.